Fiscal consolidation programs and income inequality - Brinca, Pedro (2020)
Following the Great Recession, many European countries implemented fiscal consolidation policies aimed at reducing government debt. Using three independent data sources and three different empirical approaches, we document a strong positive relationship between higher income inequality and stronger recessive impacts of fiscal consolidation programs across time and place. To explain this finding, we develop a life-cycle, overlapping generations economy with uninsurable labor market risk. We calibrate our model to match key characteristics of a number of European economies, including the distribution of wages and wealth, social security, taxes and debt, and study the effects of fiscal consolidation programs. We find that higher income risk induces precautionary savings behavior, which decreases the proportion of credit-constrained agents in the economy. Credit-constrained agents have less elastic labor supply responses to fiscal consolidation achieved through either tax hikes or public spending cuts, and this explains the relationship between income inequality and the impact of fiscal consolidation programs. Combining micro- and macro data, we find evidence of the mechanism.